Factors affecting consumers’ purchase intention towards organic skincare products / Asiah Ibrahim - Ibrahim, Asiah (Faculty of Business and Management, 2018)
This study is conducted to inspect the relationship between consumers’ purchase intention towards organic skincare products with attitude towards green brand, green brand positioning, green brand knowledge and subjective norms among consumers in Shah Alam, Selangor. The instrument used is questionnaire and the questions are adopted from several previous journals. A total of 100 sets of the questionnaire are distributed to the users and potential users of the organic skincare products for the data collection purpose. There are five variables used in this research which consists of four independent variables (with attitude towards green brand, green brand positioning, green brand knowledge and subjective norms) and an independent variable which is consumers’ purchase intention towards organic skincare products. Previous researchers found out that these independent variables have shown significant relationships with the dependent variable. The researcher used purposive sampling method in selecting the targeted respondents exclusively for this study. This study is valuable to many sources such as manufacturers and marketers to improve their strategies in gaining more potential consumers. Other than that, it is also useful to consumers to improve their knowledge and awareness about the environmental concerns. This study used Mohd Suki (2016) and Ko & Jin (2017) as the main reference which is related to the green purchase intention.